Gastrointestinal complaints in patients with anorexia nervosa in the timecourse of inpatient treatment - Riedlinger, Caroline; Mazurak, Nazar; Schäffeler, Norbert; Stengel, Andreas; Giel, Katrin Elisabeth; Zipfel, Stephan; Enck, Paul; Mack, Isabelle (Frontiers in Psychiatry, 2022)
Background: In patients with anorexia nervosa (AN), gastrointestinal (GI) symptoms are common and usually improve during or after nutritional rehabilitation. It is unclear when exactly GI symptoms change in the timecourse of treatment and to which extent. This study analyzed the timecourse of GI symptoms and their relation to disease characteristics, demographics, anthropometrical and psychological factors in inpatients with AN. Methods: In weekly intervals, the Gastrointestinal Symptom Rating Scale (GSRS) was completed and body weight measured over a mean of 9.5 weeks in inpatients with AN. Four self-report questionnaires assessing psychological factors were completed before and after inpatient treatment. Data from 38 inpatients with AN were analyzed using mixed linear models. Results: Abdominal pain and constipation improved significantly in the timecourse with 0.085 (p=.002) and 0.101 (p=.004) points per week on the GSRS scale and were predicted to normalize after 13 (p=.002) and 17 (p=.004) weeks. Total GI symptoms tended to normalize after 25 weeks (p=.079). Indigestion (borborygmus, abdominal distension, eructation, flatulence) was the most severely pathological symptom at admission and did not improve significantly (p=.197). Diarrhea and reflux were on average not pathological at admission and remained stable during treatment. Besides treatment time, the strongest predictors were ED pathology at admission for the development of abdominal pain, constipation, reflux, and total GI symptoms; stress for the development of constipation and total GI symptoms; and depression for constipation. Conclusions: Informing patients with AN about the course of GI symptoms and their improvement during weight rehabilitation may help to support compliance during treatment.